1994
DOI: 10.1287/mnsc.40.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Echelon vs. Single-Echelon Inventory Control Policies for Low-Demand Items

Abstract: Multi-echelon inventory systems are often controlled as a network of single-echelon inventory systems for simplicity of managerial authority, organizational control, and performance monitoring. This paper explores the amount of suboptimization in such a situation, using an actual demand data set provided by other researchers. We consider low-demand, high-cost items controlled on an (S - 1, S) basis, with all warehouse stockouts met on an emergency-ordering basis. We demonstrate that the suboptimality penalty f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 10 publications
0
36
1
Order By: Relevance
“…They also show that managing multi-echelon systems by using adaptations of single-location methods can be dramatically inferior to methods designed for taking advantage of a system's structure. Hausman and Erkip [6] extended the work of Muckstadt and Thomas by presenting an improved single-echelon model to approximate multi-echelon model performance. Axsäter [1] developed an alternative, exact evaluation procedure, and in addition developed an exact optimization procedure for the single-item problem.…”
Section: Introductionmentioning
confidence: 99%
“…They also show that managing multi-echelon systems by using adaptations of single-location methods can be dramatically inferior to methods designed for taking advantage of a system's structure. Hausman and Erkip [6] extended the work of Muckstadt and Thomas by presenting an improved single-echelon model to approximate multi-echelon model performance. Axsäter [1] developed an alternative, exact evaluation procedure, and in addition developed an exact optimization procedure for the single-item problem.…”
Section: Introductionmentioning
confidence: 99%
“…The model developed by Muckstadt and Thomas [1] (used for further analysis by Hausman and Erkip [14]) is an extension of the METRIC model [13] in that it allows for fast direct deliveries from the central warehouse (or even from the factory) when a demand at a local warehouse can not be met from stock on hand. It is assumed in this model that an emergency resupply order (i.e., direct delivery) that is triggered to ®ll a local demand, is always used for this purpose, even if a normal replenishment order arrives earlier at the local warehouse.…”
Section: The Muckstadt±hausman Modelmentioning
confidence: 99%
“…We will compare the numerical results of this model with the results of our model. In a later paper Hausman and Erkip [14] used the model of Muckstadt and Thomas for further analysis.…”
Section: Introductionmentioning
confidence: 99%
“…They also compare centralized and decentralized decision making. Hausman and Erkip (1994) improved the decentralized case of Muckstadt and Thomas (1980) and showed that the performance of the improved single-echelon model is within 3% and 5% of the multi-echelon model of Muckstadt and Thomas (1980). Axsäter et al (2004) considered a two-echelon inventory system in which emergency deliveries are done only from the central repair facility to the local warehouses.…”
Section: Introductionmentioning
confidence: 99%